On Kadison-Schwarz property of quantum quadratic operators on M2(C) - Mukhamedov, Farrukh; Abduganiev, Abduaziz (World Scientific, 2011)
In the present paper we first describe quantum quadratic operators (q.q.o) acting on the algebra of 2 x 2 matrices M2(C). Moreover, we provide necessary conditions for q.q.o. with Haar to satisfy Kadison-Schwarz condition. By means of such a description we give an example of q.q.o. which is not the Kadision-Schwarz operator.